Carer drinking and more serious child protection case outcomes - Laslett, Anne-Marie; Dietze, P.; Room, R. (Oxford Univeristy Press, 2013)
Care-giver 'alcohol abuse' is identified as involved in a significant proportion of child maltreatment cases internationally. This study examines how care-giver 'alcohol abuse' is related to increasing intensity of child protective intervention in a large Australian database. Predictors of child protection outcomes were examined in 38,487 Victorian state Child Protection Services (CPS) cases substantiated between 2001 and 2005. 'Likely alcohol abuse' was identified in 33 per cent of substantiations, 36 per cent of protective interventions and 42 per cent of court orders. Likely alcohol abuse was a significant predictor of more intensive official responses-protective interventions and court orders-after adjusting for 'other drug abuse' and other socio-demographic factors. Supporting multi-factorial theories of alcohol's involvement in child abuse, likely alcohol abuse was one of several risk factors that remained significant in multivariable prediction of more serious child protection outcomes.